(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Na wstępie niniejszej pracy, konieczne jest kilka słów dla bliższego określenia przedmiotu niniejszego opracowania oraz przyczyn wyboru takiego, a nie innego tematu, który - autor ma tego świadomość - w pierwszej chwili może wydać się przypadkowy. Wielokrotnie, zarówno w ostatnim okresie, jak i wcześniejszych, podkreślana jest w doktrynie prawa pewna jego ciągłość oraz pewna wspólnota idei znajdująca swoje odzwierciedlenie w wielu różnych, odległych od siebie w czasie i przestrzeni systemach prawa Historyczną ciągłość rozwoju prawa podkreślają często romaniści, ukazując zastosowanie zasad wykształconych w prawie rzymskim we współczesnych systemachprawa. Rzadziej jednak (jeżeli w ogóle) dokonywana jest analiza talciej ciągłości w przypadlm prawa polslciego, i to nie tylko przedrozbiorowego, co jest o tyle naturalne, że rozwój tego prawa został nienaturalnie przerwany, ale również prawa XX wieku. The publication is devoted to the two of key principles in modern civil law studies: principle of good faith and fair dealing as well as the principle of freedom of contract. The presentation of those principles in light of two acts of law that vary in nature and time of creation allows for demonstrating how permanent they are and how essential to the civil law of the countries with free market economy The two discussed principles have been present both in the code of obliga tions and in the Principles of European Contract Law (PECL). Their role in both acts was important and similar, though the code of obligations attached relatively smallest importance to the fair dealing principles clause. As concerns the principle of freedom of contract, the PECL have repeated the solution, the forerunners of which were, among others, the authors of the code of obligations, namely the regulation of the principles of freedom of con tract with a positive approach. The principles of good faith (in case of the PECL-also the principles of fair dealing) are visible, both under the code of obligations and the PECL, in the entire duration of the obligation relationship between the parties, starting from the moment when the parties express their intentions to the interpretation of the statements of intent (contracts) to the performance of obligations (contrac tual obligations). The conducted analysis of the code of obligations and the PECL allowed the author to bring up several theses of vital importance to the idea of trans national unification of private law and for the history of Polish law, which can be summed up in form of the following conclusions: 1. the principles lying at the foundations of the PECL have been present in the Polish law for at least several dozen years; 2. the principles of freedom of contract as well as good faith and fair deal ing, particularly important to the modern civil law studies, have played an important role in the Polish pre-war legislation as well; 3. certain solutions, relatively innovative at the time when the code of obli gations was adopted, subsequently found their regular place in the Eu ropean civil law.